Media Ular Tangga Pada Materi Komponen Biotik Dan Abiotik - Shofiyatul Laily27; Lina Arifah Fitriyah (Wacana Didaktika, 2022)
Learning media is an intermediary or message in the form of objects that can be seen and heard in order to provide effectiveness to student learning outcomes. In learning media, it is very necessary to increase efficiency during the learning process. Snakes and ladders media is an option because its use in learning can increase student activity. The purpose of research on this learning media is expected to describe the sequence of the development process in the snake ladder media material for abiotic biotic components, and can determine the validity of the development of snake ladder media. The type of research used is a development model that refers to the ADDIE research design, namely the stage (Analyze, design, development, implementation, evaluation). This research produces data in the form of a snake and ladder media development process using the ADDIE model, namely the Analyze stage, namely analyzing the material and students. Design which refers to the design of learning indicators and media to be developed. Development, namely the process of making snake and ladder media which was designed at the previous design stage. Then, the implementation stage cannot be carried out systematically, because it only reaches the validity test. Finally, evaluation, which is the final stage of snake and ladder media on biotic and abiotic component materials. In the media validation process, it is carried out by material expert validators, media experts and teachers. Then the results of the validation obtained a score of 94.6% from media experts, 82.1% by material experts, and 94.6% from science teachers. With these results, the snake and ladder media analyzed for its development process with the ADDIE approach model is declared "valid" and be able for using next learning stage. Keywords: Snakes and Ladders Media, Material, Biotic and Abiotic Components. Abstrak: Media pembelajaran merupakan perantara atau pesan berbentuk benda yang dapat dilihat dan didengar guna memberikan kefektifan pada hasil pembelajaran peserta didik. Pada pembelajaran media menjadi hal yang sangat diperlukan guna meningkatkan keefisienan selama proses belajar. Media ular tangga menjadi pilihan karena penggunaannya dalam pembelajaran dapat meningkatkan aktivitas siswa. Tujuan penelitian pada media pembelajaran ini diharapkan dapat menjabarkan runtutan proses pengembangan pada media ular tangga materi komponen biotik abiotik, serta dapat mengetahui validitas pengembangan media ular tangga. Jenis penelitian yang digunakan merupakan model pengembangan yang merujuk pada rancangan penelitian ADDIE yaitu tahap (Analyze, design, development, implementation, evaluation). Penelitian ini menghasilkan data berupa proses pengembangan media ular tangga menggunakan model ADDIE yaitu tahap Analyze yaitu menganalisis materi dan peserta didik. Design yang merujuk pada perancangan indikator pembelajaran dan media yang akan dikembangkan. Development, yakni proses pembuatan media ular tangga yang terancang pada tahap desain sebelumnya. Kemudian, tahap implementation yang belum dapat terlaksana secara sistematis, karena hanya sampai pada uji validitas saja. Terakhir, evaluation, yaitu tahap akhir media ular tangga pada materi komponen biotik dan abiotik. Pada proses validasi media, dilaksanakan oleh validator ahli materi, ahli media dan guru. Lalu pada hasil validasi tersebut diperoleh skror 94,6% dari ahli media, 82,1% oleh ahli materi, dan 94,6% dari guru IPA. Dengan hasil tersebut, maka media ular tangga yang dianalisis proses pengembangannya dengan model pendekatan ADDIE dinyatakan “valid” dan dapat dipergunakan untuk tahap pembelajaran selanjutnya.